Design & analysis of dual mode logic circuits - Chen, Yun (2019)
Dual mode logic (DML) with both static and dynamic modes is able to solve severe delay of CMOS in low voltage supply. The dissertation explores different types of DML structures and related cascading strategy by multiple times of simulation and analysis. What’s more, how to apply DML design into optimization of large-scale circuits is also explored, with a carry skip adder (CSA) as the test subject.